La herencia de Darwin y el problema de la justificación filosófico-jurídica de la Dignidad Humana - Fernandez, Atahualpa (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This study aims to examine the problem of philosophical justification and the legal theory of human dignity since a naturalistic perspective about human nature as “object” of empirical research. A concept of human dignity developed from a naturalistic approach allows to be opposed, a real and practicable form, to the evidence that human nature not only generates but guides and sets limits to the institutional and normative set that regulates its conditions of possibility.
Keywords: Law; human dignity; darwinism; human nature; moral sense